Perancangan Video Profil Museum Surabaya Berbasis Online Sebagai Upaya Mengenalkan Kepada Masyarakat di Surabaya - Pratama, Dicky Adi; Budiardjo, Hardman; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Museum of Surabaya was established since May 3rd 2015. The idea to establish the building came from the Governor of Surabaya, Tri Risma, which at the moment needed space to keep her unused belongings at the storage in her office, and realised that the Siola building was available. Surabaya citizen is clueless about the museum inside the Siola building, and the researcher wants to formulate an information to make the museum recognised by the citizen. The purpose of this Final Assignment Project is to make people aware of what remains in the museum, especially steam locomotive. By using a suitable language for teenagers, adding subtitle and transition effect in the exciting video, will hopefully deliver the purposed information. The impact of social media is insanely important for everyone. Other than searching for friends, doing online business, social media is also proved to be useful to look for new information. For that reason, the researcher wants to use the social media, moreover Youtube, as the main tool to introduce the museum to the people of Surabaya. In the making and designing the video, we have had through a complex process, such as repeating takes of pictures, then sorting it. Next thing to do was cutting and adding effect for transition like grading effect, also putting proper music to give the effect of happiness and calmness for everyone who watches it. We do hope the museum will be recognised by the society of Surabaya and they can enjoy to visit the museum in the near future.Keywords: Design, Reference Book, Traditional Dance, Bedhaya Ketawang,Supportive, Digital Imaging.